Association of the degree of food processing with the consumption of nutrients and blood pressure - Aline Rosignoli da Conceição; Poliana Cristina de Almeida Fonseca; Dayane de Castro Morais; Eliana Carla Gomes de Souza (O Mundo da Saúde, 2019)
There are many causes for hypertension, but among the modifiable factors, inadequate lifestyle is related to the higher prevalence of the disease. Therefore, the objective of this study was to evaluate the association between macro and micronutrient intake and blood pressure levels with the degree of food processing. Sixty-four adults from the rural area of ??Viçosa, Minas Gerais, Brazil were evaluated. Food consumption was assessed by a dietary recall using AVANUTRI Software, and the foods consumed were classified into three groups: in natura or minimally processed, processed and ultra-processed. Blood pressure was measured using an automatic inflation monitor. The data were analyzed in the Stata Software by means of the Student’s T test. Most of the sample consisted of female adults (64.1%) and the mean systolic and diastolic blood pressure was 122.8 mmHg (±17.1) and 77.7 mmHg (±10.9), respectively. The group of in natura or minimally processed food was responsible for the largest contribution (85.2%) of the average caloric intake (1,793.1 kcal/day), while the consumption of ultra-processed foods was only 7.7%. In addition, there was a higher intake of carbohydrate, lipid, cholesterol, polyunsaturated fat, vitamin E, potassium and sodium among individuals who consumed only in natura or minimally processed foods. Individuals who did not consume ultra-processed foods had higher intakes of vitamin E and sodium. It was concluded that there was an association between the degree of food processing and nutrient intake, however, no association was found among blood pressure levels.